Origin, diversity, and biogeography of Antarctic scale worms (Polychaeta: Polynoidae): a wide‐scale barcoding approach. Issue 7 (17th July 2022) - Cowart, Dominique A.; Schiaparelli, Stefano; Alvaro, Maria Chiara; Cecchetto, Matteo; Le Port, Anne‐Sophie; Jollivet, Didier; Hourdez, Stephane
Abstract: The Antarctic marine environment hosts diversified and highly endemic benthos owing to its unique geologic and climatic history. Current warming trends have increased the urgency of understanding Antarctic species history to predict how environmental changes will impact ecosystem functioning. Antarctic benthic lineages have traditionally been examined under three hypotheses: (1) high endemism and local radiation, (2) emergence of deep‐sea taxa through thermohaline circulation, and (3) species migrations across the Polar Front. In this study, we investigated which hypotheses best describe benthic invertebrate origins by examining Antarctic scale worms (Polynoidae). We amassed 691 polynoid sequences from the Southern Ocean and neighboring areas: the Kerguelen and Tierra del Fuego (South America) archipelagos, the Indian Ocean, and waters around New Zealand. We performed phylogenetic reconstructions to identify lineages across geographic regions, aided by mitochondrial markers cytochrome c oxidase subunit I (Cox1) and 16S ribosomal RNA (16S). Additionally, we produced haplotype networks at the species scale to examine genetic diversity, biogeographic separations, and past demography. The Cox1 dataset provided the most illuminating insights into the evolution of polynoids, with a total of 36 lineages identified. Eunoe sp. was present at Tierra del Fuego and Kerguelen, in favor of the latter acting as a migration crossroads. Harmothoe fuligineum, widespread around the Antarctic continent, was also present but isolated at Kerguelen, possibly resulting from historical freeze–thaw cycles. The genus Polyeunoa appears to have diversified prior to colonizing the continent, leading to the co‐occurrence of at least three cryptic species around the Southern and Indian Oceans. Analyses identified that nearly all populations are presently expanding following a bottleneck event, possibly caused by habitat reduction from the last glacial episodes. Findings support multiple origins for contemporary Antarctic polynoids, and some species investigated here provide information on ancestral scenarios of (re)colonization. First, it is apparent that species collected from the Antarctic continent are endemic, as the absence of closely related species in the Kerguelen and Tierra del Fuego datasets for most lineages argues in favor of Hypothesis 1 of local origin. Next, Eunoe sp. and H. fuligineum, however, support the possibility of Kerguelen and other sub‐Antarctic islands acting as a crossroads for larvae of some species, in support of Hypothesis 3. Finally, the genus Polyeunoa, conversely, is found at depths greater than 150 m and may have a deep origin, in line with Hypothesis 2. These "non endemic" groups, nevertheless, have a distribution that is either north or south of the Antarctic Polar Front, indicating that there is still a barrier to dispersal, even in the deep sea. Abstract : We used scale worms as a representative group for Antarctic marine benthic animals to better understand their evolutionary history, and possibly predict how  they could respond to warming temperatures. Using genetic barcode data from over 600 scale worms, we were able to comprehend the history of this group during past warming and cooling geological periods. These events had profound effects on the genetic diversity of scale worms that are still detectable in present populations. For one, the geographic separation made by the Antarctic Circumpolar Current identified that northern animals are unlikely to colonize waters off of the Antarctic continent, raising concerns for the future of colder biological communities in times of warming.